A radical tricationic rhomboid tetraborane(4) with four-center, five-electron bonding - Litters, Sebastian; Kaifer, Elisabeth; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2016)
The red-colored tetraborane(4) [B4(hpp)4]3+. (3; hpp=1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate) with a rhomboid B4 skeleton stabilized by four N donors, was synthesized by the reaction of the strong hydride abstraction reagent [(acridine)BCl2][AlCl4] with the electron-rich diborane(4) [HB(hpp)]2 (1). The salt 3[AlCl4]3 was structurally characterized and the presence of unpaired electrons proven by EPR measurements. The unprecedented radical tricationic 3 is distinguished by a high positive charge and boron atoms in a low oxidation state (less than two).